Global Land Outlook: Thematic Report on Rangelands and Pastoralists - Herrera Calvo, Pedro Maria (United Nations Convention to Combat Desertification, 2024)
The report explores the complex environmental, social, and economic dimensions that link rangelands and local communities. It describes the important role and untapped potential of pastoralism and extensive livestock management systems to contribute to a just transition, climate resilience, and more equitable rural development, recognising that many of the challenges confronting rangelands originate beyond local communities and are not under their control. Drawing on case studies submitted from around the world, the report offers new perspectives on how pastoralism can contribute to more effective rangeland governance and stewardship and examines the potential for replicability and scalability. It draws on a diversity of approaches (e.g., territorial, ecosystem, cultural) and initiatives (e.g., global, national, local), supported by policy, implementation, and investment frameworks, to conserve, sustainably manage, and restore rangelands.